Peran Pembiayaan Keuangan Mikro Syariah dan Pendampingan Usaha terhadap Kesejahteraan Masyarakat - Divani Nuril Khaqiqi; Miswan Ansori (CV. Creative Tugu Pena, 2024)
This study aims to analyze the effect of sharia financing and business assistance on community welfare carried out by BMT AL Hikmah Guyangan branch in Guyangan Village, Jepara Regency. Through an associative quantitative approach, data were collected from 94 respondents of sharia cooperative members who received financing and business assistance. The results of multiple linear regression analysis indicate that sharia financing has a significant effect on improving community welfare. In addition, business assistance also has a positive impact on welfare. The combination of sharia financing and business assistance simultaneously makes a significant contribution to improving community welfare. These findings underline the importance of the role of sharia cooperatives in strengthening the welfare and financial inclusion of communities in rural areas.